Separation of Fine Particles from Gas in Paint-Spraying Booths - Bikkulov Rustem Ya. (EDP Sciences, 2021)
Nowadays, at production facilities with paint-spraying booths that use paint and varnish materials to cover the surfaces of product, the problem of gas flow contamination with finely dispersed solid particles of dust and rubbish, which negatively affect the quality of products, is increasingly being raised. In order to minimize the content of solid particles in the gas flow, coarse and fine filters are installed in the paint-spraying booths, which prevent dust particles from entering the surface of products. However, the existing purification devices have a number of disadvantages that affect the efficiency of collecting finely dispersed particles from the gas flow with a size of 0.5-5 microns. The authors of article developed a square separator to increase the efficiency of collecting finely dispersed particles from gas flows in the paint-spraying booths. The installation of proposed separation device in the paint-spraying booths affects not only the quality of collecting solid particles, but also increases the service life of fine and coarse filters In the course of numerical studies, the results of impact of structural and technological parameters, namely, the impact of inlet rate and scale of separation device on the efficiency of collecting solid particles from the gas flow, were obtained.